Schaum's outline of theory and problems of linear algebra - Lipschutz, Seymour; Lipson, Marc Lars (Boston : McGraw-Hill, 2001)
Mathematics and Statistics
Keywords: Linear algebra; Spatial vectors; Matrices; Linear equations; Linear mappings; Determinants; Multilinear products